Gracchus Babeuf et le communisme - Lévi-Strauss, Claude (Bruxelles : L'Églantine, 1926)
Collectie Vrijzinnige Werkmansbibliotheek
Frans
Monografie
Keywords: Babeuf, Gracchus; Vrijzinnige Werkmansbibliotheek; communisme